The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1590/abd1806-4841.20175996
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Kamino bodies: a little-known histological finding. Prevalence in 19 cases of Reed nevus

Abstract: The present study aimed to determine the prevalence of Kamino bodies in Reed nevus, since most studies to date show conflicting data on this issue. This was a retrospective observational study, in which the histopathology of 19 Reed nevus lesions were reviewed. The slides were stained by hematoxylin and eosin and periodic acid-Schiff, with a special focus placed on the identification of Kamino bodies. Some clinical data were also collected. The median patient age was 12 years (range of 2 to 58). The women to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Criteria should be carefully considered and combined. These initial melanomas may be incompletely developed melanomas [ 34 ]. Woltsche et al ., in a review, reanalysed melanocytic lesions and reaffirmed that there are lesions that cannot be classified using the clinical, dermatoscopic and histopathological criteria; such lesions would be termed atypical melanocytic proliferations of uncertain significance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Criteria should be carefully considered and combined. These initial melanomas may be incompletely developed melanomas [ 34 ]. Woltsche et al ., in a review, reanalysed melanocytic lesions and reaffirmed that there are lesions that cannot be classified using the clinical, dermatoscopic and histopathological criteria; such lesions would be termed atypical melanocytic proliferations of uncertain significance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the dermoscopy, a corresponding diagnosis for pigmented skin diseases can be given, and a more accurate treatment method for skin diseases can be offered. It expands the scope and depth of the doctor's observation of skin lesions effectively, fills the limitations of visual observation, and provides reliable evidence for clinical diagnosis and treatment [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Some authors also reported such bodies in malignant melanoma. [ 34 ] Lafora bodies: These are intracytoplasmic, basophilic and metachromatic, PAS-positive and diastase-resistant, concentric target-like laminated inclusions which are found in the skin (excretory sweat ducts), neurons, muscle cells, and hepatocytes in patients with Lafora body disease. [ 17 ] Leishman-Donovan (LD) bodies: In untreated patients of leishmaniasis, LD bodies appear as light blue, ellipsoid bodies, 2–4 μm long, with an eccentric nucleus and a smaller kinetosome at the opposite pole within large macrophages (Wright's cells) [ Figure 7 ].…”
mentioning
confidence: 99%